Modelling emotion expression through agent oriented methodology - S.Filzah Zulkifli; CW Shiang; N Jali; M.A. Khairuddin (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents Modelling Emotion Expression through Agent Oriented Methodology. Considering emotions of the intended users in the software engineering can uncover new requirements to improve and more accepted the system. While emotion is paying much attention nowadays, there is lacking systematic way to model the emotion based system. Without the systematic approach, it is hard to debug, design and develop an emotion based system. Since the emotional requirement of people has not being fully investigated, the research outcome propose the emotion modelling as part of the complete set of agent-oriented modelling for virtual character in eLearning system, The contribution of this paper is to introduce agent oriented modelling to systematic model an emotion based solution for an eLearning system and instructional video design. With the emotion model, it can serve as a guide to design, redesign, and discuss the emotion elements among the software development team. This is important for better debugging and project management especially for emotion led system.